System integration : from transistor design to large scale integrated circuits - Hoffmann, Kurt, 1951- (John Wiley & Sons, 2004)
The development of large-scale integrated systems on a chip has had a dramatic effect on circuit design methodology. Recent years have seen an escalation of interest in systems level integration (system-on-a-chip) and the development of low power, high chip density circuits and systems. Kurt Hoffmann sets out to address a wide range of issues relating to the design and integration of integrated circuit components and provides readers with the methodology by which simple equations for the estimation of transistor geometries and circuit behaviour can be deduced. The broad coverage of this unique.